A Reconfigurable Spiral Antenna for Adaptive MIMO Systems. Issue 3 (1st August 2005) - Cetiner, Bedri A.; Qian, J. Y.; Li, G. P.; De Flaviis, F.
Abstract : We present a reconfigurable spiral antenna for use in adaptive MIMO systems. The antenna is capable of changing the sense of polarization of the radiated field. It is fabricated by using an RF-MEMS technology compatible with microwave laminate substrates developed within the author's group. The proposed antenna structure is built on a number of rectangular-shaped bent metallic strips interconnected to each other with RF-MEMS actuators. Two senses of polarization, RHCP and LHCP, are achieved by configuring the physical structure of the antenna, that is, by changing the winding sense of the spiral, through judicious activation of MEM actuators. The fabrication process for the monolithic integration of MEM actuators with bent microstrip pixels on RO4003-FR4 microwave laminate substrate is described. The measured and calculated radiation and impedance characteristics of the antenna are given. The operating frequency of the presented antenna design can easily be adjusted to be compatible with popular IEEE networking standards such as 802.11a.